Comparison of the Efficacy of Transthoracic Cannulation into the Ascending Aorta Versus Femoral Artery Cannulation in Minimally Invasive Cardiac Surgery. Issue 6 (December 2019) - Nakajima, Hiroyuki; Takazawa, Akitoshi; Tounaga, Chiho; Yoshitake, Akihiro; Tochii, Masato; Hayashi, Jun; Kaneyuki, Daisuke; Asakura, Toshihisa; Iguchi, Atsushi
Objective: To delineate the efficacy and safety of transthoracic cannulation to the ascending aorta through a right pleural cavity during minimally invasive cardiac surgery (MICS). Methods: We retrospectively assessed the records of 104 patients who underwent MICS in our institution between December 2011 and December 2018. Procedures included mitral valve repair (88 patients), aortic valve replacement (8 patients), atrial septal defect closure (6 patients), and myxoma resection (2 patients). Aortic valve replacements were performed through the third intercostal space (ICS), whereas the other procedures were mainly performed through the fourth ICS. The femoral group comprised 60 patients in whom an artificial graft was anastomosed to the femoral artery and 4 who underwent cannulation into the femoral artery. The aorta group comprised 40 patients in whom transthoracic cannulation was performed through the second or third ICS, separate from the main skin incision. Results: No mortality or critical complications were associated with cardiopulmonary bypass. Perfusion pressure measured at outflow of the artificial lung (224 ± 43 vs. 190 ± 42; P < 0.001) and pump pressure measured at the outflow of the pump (293 ± 50 vs. 255 ± 57; P < 0.001) were significantly higher in the femoral group than in the aorta group. The skin incision lengths were similar (56.9 ± 6.9 vs. 55.1 ± 6.0 mm; P = 0.107). Conclusions: Transthoracic cannulation into the ascending aorta is reliable and can be safely performed. The possible risks associated with peripheral cannulation and retrograde perfusion can be avoided thereafter.